Parents' Shift Work in Connection with Work–Family Conflict and Mental Health: Examining the Pathways for Mothers and Fathers. (February 2021) - Zhao, Yixuan; Cooklin, Amanda R.; Richardson, Alice; Strazdins, Lyndall; Butterworth, Peter; Leach, Liana S.
Shift work might aggravate work–family conflict and mental health. The current study used moderated-mediation analyses to investigate the association between shift work and mental health, whether work–family conflict explained this association, and whether the pathways differed between genders. The sample included 756 mothers and 452 fathers participating in the "Families at Work" survey, an online nationwide community-based survey of employed parents. The findings highlight the complex interplay between parents' work schedules, work–family conflict and psychological distress. They show some evidence that working irregular shifts was associated with higher work–family conflict in connection with higher psychological distress, with fathers at greater risk. Working regular shifts was associated with poorer mental health, but this was not related to increased work–family conflict, and this association was stronger for mothers. As the labor force becomes increasingly fractured, it is critical that the impacts of non-standard work schedules continue to be considered.